Impact of Community Health Workers on Elderly Patients' Advance Care Planning and Health Care Utilization: Moving the Dial. Issue 4 (April 2017) - Litzelman, Debra K.; Inui, Thomas S.; Griffin, Wilma J.; Perkins, Anthony; Cottingham, Ann H.; Schmitt-Wendholt, Kathleen M.; Ivy, Steven S.
Abstract : Background: Advance care planning (ACP) is recommended for all persons to ensure that the care they receive aligns with their values and preferences. Objective: To evaluate an ACP intervention developed to better meet the needs and priorities of persons with chronic diseases, including mild cognitive impairment. Research Design: A year-long, pre-post intervention using lay community health workers [care coordinator assistants (CCAs)] trained to conduct and document ACP conversations with patients during home health visits with pre-post evaluation. Subjects: The 818 patients were 74.2 years old (mean); 78% women; 51% African American; 43% white. Measures: Documentation of ACP conversation in electronic health record fields and health care utilization outcomes. Results: In this target population ACP documentation rose from 3.4% (pre-CCA training) to 47.9% (post) of patients who had at least 1 discussion about ACP in the electronic health record. In the 1-year preintervention period, there were no differences in admissions, emergency department (ED) visits, and outpatient visits between patients who did and did not have ACP discussion. After adjusting for prior hospitalization and ED use histories, ACP discussions were associated with a 34% less probability of hospitalization (hazard ratios, 0.66; 95% confidence interval, 0.45–0.97), and similar effects are apparent on ED use independent of age and prior ED use effects. Conclusions: Patients with chronic diseases including mild cognitive impairment can engage in ACP conversations with trusted home health care providers. Having ACP conversation is associated with significant reduction in seeking urgent health care and in hospitalizations. Abstract : Supplemental Digital Content is available in the text.